AI Applications in Logistics and Supply Chain Management in Vietnam - Hieu, Truong Trung; Phi, Pham Trinh Hong (International Journal of Research and Applied Technology (INJURATECH), 2025)
In the context of strong digital transformation in all fields in Vietnam, especially the application of artificial intelligence (AI) in all fields, including the logistics and supply chain industry in Vietnam. This study examines the main objective of synthesizing theories to evaluate the impacts of AI in the field of logistics and supply chain management. The research results show that the implementation of AI can bring significant benefits to businesses in key functions such as: demand forecasting, transportation optimization, inventory management, order monitoring and tracking, warehouse automation and risk analysis. With a systematic literature review method, through the synthesis of reputable domestic and foreign studies and reports to analyze the potential application of AI in the logistics and supply chain industry. At the same time, the article discusses the challenges and recommendations to promote digital transformation in the logistics field effectively and sustainably. Thereby, the article presents the benefits achieved and the challenges to overcome, and evaluates the development potential in Vietnam and in the world.